Evaluation of the productivities of Maure and Peul cattle breeds at the Sahelian station, Niono, Mali - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Presents the results of a study carried out to evaluate the productivities of the Maure and Peul breeds and some of their crosses in a semi-arid environment, at the Sahelian station and Niono ranch, Mali. Describes the production system at Niono (1966-1975). Examines reproductive performance, milk yield & composition, viability, body weight, and maternal ability. Compares production systems in environments similar to that of Niono.